The effect of the per formative (kinesthetic) and visual encoding strategy for learning some football skills (Journal of the College of Basic Education, 2024)
The current study aimed to prepare an educational curriculum according to the strategy of (performative, motor, and visual encoding) to learn some football skills (handling, scoring, and dribbling). The researcher used the experimental approach by designing two equal groups with pre- and post-tests, as the research sample represented third-stage students. / Morning study, Department of Physical Education and Sports Sciences at the College of Basic Education/Al-Mustansiriya University, numbering (60) students, divided into two groups, each group (30) students, where the results of the tests showed that there are statistically significant differences between the results of the two groups (experimental and control) For the benefit of the experimental group, the researcher concluded some recommendations, including the necessity of benefiting from the visual (kinesthetic) encoding strategy due to its positive impact on learning skills (handling, scoring, dribbling) in football.